(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the problems of the study of oikonyms in various languages. The idea is substantiated that the character of oikonyms is influenced by the structure of the language, its imagery, grammatical structure, interaction with other languages, as well as the natural environment in which native speakers live. The style of thinking, perception of the world through images and representations are reflected in the names of the geographical environment, their preservation and use in everyday life, as well as in artistic practice. The use of oikonyms, their transfer from one language to another, and the nature of the distortions that manifest themselves depend on the group and language family to which they belong.